Factors of Risk Associated with Bullying in School-Age Children: A Systematic Review - Eni Hidayati; Alifiati Fitrikasari; Hastaning Sakti; Nur Setiawati Dewi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Children in school frequently look to others for approval and take pride in their achievements. The Objective: The purpose of this research is to analyze the impact of bullying on mental and physical health and to understand ways to prevent bullying. Methods: Using a systematic review methodology, the study drew information from secondary sources found by using keyword searches in databases like Garuda, Science Direct, Sinta, and PubMed, search for journal articles for 2018-2023, and 15 articles that met the inclusion criteria were reviewed. The journals' classification, language, and year of publication were taken into consideration when selecting the papers. The study topic was formulated using the Pico framework, and search strategies were developed by incorporating Boolean operators (or, and, not) to achieve a more complete search. The search, selection, and analysis of pertinent literature were conducted rigorously in the review by adhering to the prisma. Results: Ten publications in all fulfilled the requirements for inclusion in the systematic review. Psychological problems such despair, anxiety, low self-esteem, social disengagement, feelings of isolation, difficulty focusing, scholastic decline, emotional instability, behavioral changes, and suicidal thoughts were among the many themes discussed in the papers. Furthermore, five research emphasized the detrimental effects of bullying on one's physical health, including headaches, insomnia, digestive troubles, respiratory problems, anorexia, back pain, and chest pain. Conclusion: Bullying has a major negative impact on a child's physical and mental health when they are in school. The risk factors that have been found offer significant insights into the dynamics of bullying behavior, which has implications for methods related to prevention and intervention.